Cotranscriptional Production of Chemically Modified RNA Nanoparticles - Kireeva, Maria L. (Methods Mol Biol, 2017)
RNA nanoparticles consisting of multiple RNA strands of different sequences forming various three-dimensional structures emerge as promising carriers of siRNAs, RNA aptamers, and ribozymes. In vitro transcription of a mixture of dsDNA templates encoding all the subunits of the RNA nanoparticle may result in cotranscriptional self-assembly of the nanoparticle. Based on our experience with production of RNA nanorings, RNA nanocubes, and RNA three-way junctions, we propose a strategy for optimization of the cotranscriptional production of chemically modified ribonuclease-resistant RNA nanoparticles.